Preparation method of antibacterial modified ion exchange resin
By modifying the surface oxidation and amination of the ion exchange resin, combined with the reaction of quaternary ammonium and epoxy, stable antibacterial functional groups are formed, which solves the problems of bacterial growth and antibacterial loss on the surface of the resin, and achieves effective antibacterial effects and Distribution of long-lived antibacterial agents.
Patent Information
- Application Number
- CN202310830625.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
AI Technical Summary
Existing ion exchange resins are prone to breed bacteria during use, resulting in the total number of colonies in drinking water and bacterial metabolites exceeding the standard, and antibacterial agents of antibacterial materials on the market are easily lost, making it difficult to achieve a balance between antibacterial effect and soaking requirements.
Through surface oxidation and amine modification, the ion exchange resin is placed in an acid solution and an amine-based modified solution for treatment, followed by a water bath reaction in a quaternary ammonium and epoxy modified solution to form a stable antibacterial functional group to ensure that Antibacterial agents are not easily lost.
Effective inhibition of bacteria is achieved, bacterial breeding and bacterial metabolites are prevented, and the chemical bonds of antibacterial agents are stable, reducing the loss rate and improving service life.
Abstract
Description
Technical Field
[0001] The invention relates to the field of ion exchange resins, and in particular to a method for preparing an antibacterial modified ion exchange resin. Background Art
[0002] Ion exchange resins are widely used in household water softeners, water filter pitchers, and the end filters of household water purifiers to remove water hardness, alkalinity, heavy metals and other substances, thereby improving water quality and reducing the risk of water scaling. However, during the use of ion exchange resins, since the material itself does not have antibacterial properties, bacteria may grow, causing the total colony count and bacterial metabolites (such as nitrite) in drinking water to exceed the standard, and in extreme cases, the drinking water may become smelly.
[0003] For example, the Chinese invention patent "A method for producing a mesoporous tourmaline composite polystyrene multi-copolymer ion exchange resin" with application publication number CN106220770A discloses a method for producing a mesoporous tourmaline composite polystyrene multi-copolymer ion exchange resin, the specific steps of which include the preparation of an aqueous phase and an oil phase, the preparation of composite resin microspheres and the synthesis of ion exchange resins, wherein the resin microsphere skeleton is cross-linked by styrene, methyl methacrylate and vinyl trimethoxysilane. The polystyrene multi-copolymer ion exchange resin of the invention has high mechanical strength, good pore size uniformity, high ion exchange capacity, and can also play an antibacterial and water purification role; however, since the ion exchange resin itself does not have antibacterial properties, it is easy to breed bacteria, resulting in excessive total colony counts in the water.
[0004] In the field of water purification, the commonly used inorganic antimicrobial agents are mainly zinc and silver. However, due to the limitation of sanitary standards for domestic water supply and distribution, the increase of silver ions in water-related materials must be less than 5ppb, and the increase of zinc ions must be less than 200ppb. It is difficult for the materials on the market to achieve a balance between the antibacterial effect and the soaking requirements. In addition, the antibacterial agent of physically blended antibacterial materials is lost quickly and has a short service life. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing an antibacterial modified ion exchange resin having an antibacterial agent that is not easy to lose in view of the above-mentioned situation.
[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing an antibacterial ion exchange resin, characterized in that it comprises the following steps:
[0007] ① Raw material preparation: rinse the ion exchange resin with distilled water to remove the surface scum and impurities; filter and dry;
[0008] ② Acidification modification: Soak the ion exchange resin raw material in an acid solution to obtain an acidified ion exchange resin;
[0009] ③ Surface modification: The acidified ion exchange resin is placed in an amine modification solution, heated, cleaned and dried to obtain an ion exchange resin with an amino-modified surface.
[0010] ④ Antibacterial modification: The amino-modified primary ion exchange resin is placed in a modification solution containing quaternary ammonium and epoxy groups, reacted in a water bath, and then washed and dried to obtain an antibacterial ion exchange resin.
[0011] The surface oxidation modified and antibacterial modified solutions in the preparation process of modified ion exchange resin can be recycled, which reduces production costs, reduces waste liquid discharge, and is more environmentally friendly.
[0012] Preferably, the particle size of the ion exchange resin in step ① is 0.3-1.2 mm.
[0013] Preferably, the ion exchange resin in step ① has a volume exchange capacity of ≥1.4 mmol / mL, a water content of 40% to 60%, and a density of 0.7 to 0.8 g / mL.
[0014] Preferably, the acid in step ② is a mixture of one or more of hydrochloric acid, nitric acid and sulfuric acid; the ion exchange resin raw material is immersed in the acid solution for 30 to 90 minutes.
[0015] Preferably, the pH of the acid solution in step ② is 2-5.
[0016] Preferably, in the amine-modified solution of step ③, the solute is a mixture of one or more of ethylenediamine, chitosan, piperazine, N-carboxymethyl chitosan, polyethyleneimine, polyallylamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyvinyl imidazole, p-aminobenzene, m-aminobenzene, and polyvinylpyrrolidone.
[0017] Preferably, the solvent in step ③ is water, or the solvent is a mixture of one or more of methanol, ethanol, acetone and water.
[0018] Preferably, the concentration of the amine-modified solution in step ③ is 0.5-5wt%.
[0019] Preferably, the heating in step ③ is: heating in a water bath at 50-90° C. for 12-24 h.
[0020] Preferably, the concentration of the solution containing quaternary ammonium and epoxy groups in step ④ is 2-9wt%.
[0021] Preferably, the solute of the modified solution containing quaternary ammonium and epoxy groups in step ④ is a mixture of one or more of glycidyltrimethylammonium chloride, glycidyltriethylammonium chloride and glycidyldimethyldodecylammonium chloride.
[0022] Preferably, the solvent of the solution containing quaternary ammonium and epoxy groups in step ④ is water.
[0023] Preferably, the preparation of the antibacterial modified ion exchange resin may specifically adopt the following technical contents: comprising the following steps:
[0024] ① Raw material preparation: rinse the ion exchange resin with distilled water several times to remove the surface scum and impurities; filter, dry at 60°C for 12 hours, bag and put into a dryer for standby use; the particle size of the ion exchange resin is between 0.3 and 1.2 mm, the volume exchange capacity is greater than 1.4 mmol / mL, the water content is 40% to 0%, and the density is 0.7 to 0.8 g / mL. The model of the ion exchange resin can be Lewatit S-8227 from Lanxess.
[0025] ② Acidification modification: Soak the ion exchange resin raw material in an acid solution. The acid can be hydrochloric acid, nitric acid, sulfuric acid, etc. The pH is controlled between 2 and 5. The soaking time is 30 to 90 minutes. Introduce carboxyl groups on the resin surface; the chemical reaction equation is: R-COONa + H + =R-COOH + Na + .
[0026] ③ Surface modification: The acidified ion exchange resin is placed in a 0.5-5wt% amine modification solution, heated in a water bath at 50-90°C for 12-24h, washed and dried. Since the amine groups can react with the surface carboxyl groups of the modified ion exchange resin, an ion exchange resin with an amino-modified surface is obtained.
[0027] ④ Antibacterial modification: Place the aminated ion exchange resin in a 2-9wt% modification solution containing quaternary ammonium and epoxy groups, react in a water bath at 35-80°C for 6-12h, wash and dry. In the aminated ion exchange resin, the lone pair of electrons can attack the epoxy group, and the two can react chemically to obtain the final antibacterial ion exchange resin. The antibacterial functional groups in the ion exchange resin are linked to the surface of the ion exchange resin due to chemical reactions, and their force is very stable and not easy to lose.
[0028] Compared with the prior art, the advantages of the present invention are:
[0029] Quaternary ammonium materials can directly attack the cell wall and cell membrane of bacteria, thereby achieving the purpose of antibacterial; the prepared ion exchange resin has an antibacterial effect, which can effectively prevent the growth of bacteria on the surface of the ion exchange resin and the production of bacterial metabolites. Moreover, the present invention makes the antibacterial material evenly distributed on the surface of the ion exchange resin by combining surface segregation with chemical modification. Subsequently, the antibacterial material is introduced by means of chemical modification, and the chemical bond formed is very stable, so that the antibacterial agent is not easy to be lost. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below with reference to the embodiments.
[0031] Example 1
[0032] After washing, the ion exchange resin with a particle size of 0.8 mm, a volume exchange capacity of 1.6 mmol / mL, a water content of 40%, and a density of 0.8 g / mL was soaked in hydrochloric acid with a pH of 4 for 60 minutes to oxidize the surface of the ion exchange resin and generate a large number of oxygen-containing functional groups such as carboxyl and carbonyl. The oxidized ion exchange resin was placed in a 4wt% water-methanol solution of polyethyleneimine, with a volume ratio of water to methanol of 1:1; reacted at 90°C for 12 hours, and after washing, the aminated primary ion exchange resin was placed in a 6wt% aqueous solution of epoxypropyltrimethylammonium chloride, reacted at 60°C for 6 hours, and washed and dried to obtain the final antibacterial ion exchange resin. The antibacterial rate of the antibacterial ion exchange resin against Escherichia coli is 99.9%, and the antibacterial rate against Staphylococcus aureus is 99.8%. The antibacterial agent loss rate was 0.9% when compared before and after the test.
[0033] Example 2
[0034] After washing, the ion exchange resin with a particle size of 0.7 mm, a volume exchange capacity of 1.4 mmol / mL, a water content of 60%, and a density of 0.8 g / mL was placed in hydrochloric acid at pH = 4 for 60 minutes to oxidize the surface of the ion exchange resin and generate a large number of oxygen-containing functional groups such as carboxyl and carbonyl. The oxidized ion exchange resin was placed in a 2wt% aqueous solution of triethylenetetramine and reacted at 50°C for 24 hours. After washing, the aminated primary ion exchange resin was placed in a 9% aqueous solution of glycidyltriethylammonium chloride and reacted at 80°C for 12 hours. After washing and drying, the final antibacterial ion exchange resin was obtained. The antibacterial rate of the antibacterial ion exchange resin against Escherichia coli was 99.2%, and the antibacterial rate against Staphylococcus aureus was 99.8%. The antibacterial agent loss rate was 0.6% when compared before and after the test.
[0035] Example 3
[0036] After washing, the ion exchange resin with a particle size of 0.8 mm, a volume exchange capacity of 1.4 mmol / mL, a water content of 50%, and a density of 0.7 g / mL was placed in hydrochloric acid at pH = 4 for 60 minutes to oxidize the surface of the ion exchange resin and generate a large number of oxygen-containing functional groups such as carboxyl and carbonyl. The oxidized ion exchange resin was placed in a 1wt% water-methanol solution of polyvinyl imidazole, with a volume ratio of water to methanol of 1:2; reacted at 70°C for 15 hours, and after washing, the aminated primary ion exchange resin was placed in a 3wt% aqueous solution of epoxypropyl dimethyl dodecyl ammonium chloride, reacted at 70°C for 12 hours, and washed and dried to obtain the final antibacterial ion exchange resin. The antibacterial rate of the antibacterial ion exchange resin against Escherichia coli was 99.6%, and the antibacterial rate against Staphylococcus aureus was 99.9%. The antibacterial agent loss rate was 0.3% when compared before and after the test.
[0037] Example 4
[0038] After washing, the ion exchange resin with a particle size of 0.8 mm, a volume exchange capacity of 1.4 mmol / mL, a water content of 60%, and a density of 0.8 g / mL was placed in hydrochloric acid at pH = 4 for 60 minutes to oxidize the surface of the ion exchange resin and generate a large number of oxygen-containing functional groups such as carboxyl and carbonyl. The oxidized ion exchange resin was placed in a 1wt% water-methanol solution of polyvinyl imidazole, with a volume ratio of water to methanol of 1:2; reacted at 70°C for 15 hours, and after washing, the aminated primary ion exchange resin was placed in a 3wt% aqueous solution of epoxypropyl dimethyl dodecyl ammonium chloride, reacted at 35°C for 12 hours, and washed and dried to obtain the final antibacterial ion exchange resin. The antibacterial rate of the antibacterial ion exchange resin against Escherichia coli was 99.8%, and the antibacterial rate against Staphylococcus aureus was 99.3%. The antibacterial agent loss rate was 0.5% when compared before and after the test.
[0039] Example 5
[0040] After washing, the ion exchange resin with a particle size of 0.3 mm, a volume exchange capacity of 1.4 mmol / mL, a water content of 60%, and a density of 0.8 g / mL was placed in nitric acid at pH = 2 for 30 minutes to oxidize the surface of the ion exchange resin and generate a large number of oxygen-containing functional groups such as carboxyl and carbonyl. The oxidized ion exchange resin was placed in a water-methanol solution of 0.5 wt% polyvinyl imidazole, with a volume ratio of water to methanol of 1:2; reacted at 70 ° C for 15 hours, and after washing, the aminated primary ion exchange resin was placed in a 9 wt% epoxypropyl dimethyl dodecyl ammonium chloride aqueous solution, reacted at 35 ° C for 10 hours, and washed and dried to obtain the final antibacterial ion exchange resin. The antibacterial rate of the antibacterial ion exchange resin against Escherichia coli was 99.9%, and the antibacterial rate against Staphylococcus aureus was 99.7%. The antibacterial agent loss rate was 0.4% when compared before and after the test.
[0042] Example 6
[0043] After washing, the ion exchange resin with a particle size of 1.2 mm, a volume exchange capacity of 1.4 mmol / mL, a water content of 60%, and a density of 0.8 g / mL was placed in sulfuric acid at pH = 5 for 90 minutes to oxidize the surface of the ion exchange resin and generate a large number of oxygen-containing functional groups such as carboxyl and carbonyl. The oxidized ion exchange resin was placed in a 5wt% water-methanol solution of polyvinyl imidazole, with a volume ratio of water to methanol of 1:2; reacted at 70°C for 15 hours, and after washing, the aminated primary ion exchange resin was placed in a 2wt% epoxypropyl dimethyl dodecyl ammonium chloride aqueous solution, reacted at 80°C for 6 hours, and washed and dried to obtain the final antibacterial ion exchange resin. The antibacterial rate of the antibacterial ion exchange resin against Escherichia coli is 99.6%, and the antibacterial rate against Staphylococcus aureus is 99.1%. The antibacterial agent loss rate was 0.6% when compared before and after the test. ;
[0044] Comparative Example 1
[0045] After washing, the ion exchange resin with a particle size of 0.8 mm, a volume exchange capacity of 1.4 mmol / mL, a water content of 60%, and a density of 0.8 g / mL was placed in pH = 4 hydrochloric acid for 60 minutes to oxidize the surface of the ion exchange resin and generate a large number of oxygen-containing functional groups such as carboxyl and carbonyl. The oxidized ion exchange resin was placed in a 4wt% water-methanol solution of polyethyleneimine, with a volume ratio of water to methanol of 1:1, and reacted at 90°C for 12 hours. After washing, the aminated primary ion exchange resin was placed in a 6wt% aqueous solution of epoxypropyltrimethylammonium chloride, reacted at 40°C for 12 hours, and washed and dried to obtain the final antibacterial ion exchange resin. The antibacterial rate of the antibacterial ion exchange resin against Escherichia coli was 66.2%, and the antibacterial rate against Staphylococcus aureus was 74.4%. The antibacterial agent loss rate was 16.6% when compared before and after the test.
[0046] Comparative Example 2
[0047] The ion exchange resin washed with distilled water was placed in a 1wt% water-methanol solution of polyvinyl imidazole, wherein the volume ratio of water to methanol was 1:2; reacted at 70°C for 15h, and after washing, the aminated primary ion exchange resin was placed in a 3wt% aqueous solution of epoxypropyl dimethyl dodecyl ammonium chloride, reacted at 70°C for 15h, and washed and dried to obtain the final ion exchange resin. The antibacterial rate of the ion exchange resin against Escherichia coli was 10.2%, and the antibacterial rate against Staphylococcus aureus was 19.1%. The antibacterial agent loss rate was 60.9% when compared before and after the test.
[0048] Comparative Example 3
[0049] After washing, the ion exchange resin with a particle size of 0.8 mm, a volume exchange capacity of 1.4 mmol / mL, a water content of 60%, and a density of 0.8 g / mL was placed in a pH = 4 hydrochloric acid for 60 minutes to oxidize the surface of the ion exchange resin to generate a large number of oxygen-containing functional groups such as carboxyl and carbonyl. After washing, the oxidized ion exchange resin was placed in a 3wt% aqueous solution of epoxypropyl dimethyl dodecyl ammonium chloride, reacted at 70°C for 15 hours, and the final antibacterial ion exchange resin was obtained after washing and drying. The antibacterial rate of the antibacterial ion exchange resin against Escherichia coli is 13.2%, and the antibacterial rate against Staphylococcus aureus is 17.1%. Comparison before and after the test shows that the loss rate of the antibacterial agent is 61.5%.
[0050] As can be seen from Examples 1-6, the antibacterial agent loss rate of the present invention is low. As can be seen from Comparative Example 3, when the reaction temperature of the final quaternization is low, the reactivity of the amine group and the epoxy functional group is low, so that the antibacterial agent cannot be effectively loaded onto the surface of the ion exchange resin, the overall antibacterial rate of the ion exchange resin is reduced, and the antibacterial agent loss rate is increased.
[0051] From Examples 1-6, Comparative Examples 2 and 3, it can be seen that the two steps of surface oxidation and amination modification of the ion exchange resin are indispensable. If one of them is missing, the obtained ion exchange resin does not have an antibacterial effect. If the oxidation treatment is not performed, the surface of the ion exchange resin cannot obtain enough oxygen-containing functional groups that react with the amine group, and the antibacterial agent cannot be loaded; if the amination modification is not performed, the antibacterial agent cannot effectively react with the ion exchange resin, the antibacterial agent loss rate is high, and the obtained ion exchange resin has no antibacterial effect.
Claims
1. A method for preparing an antibacterial ion exchange resin, characterized in that: The steps include: ① Raw material preparation: rinse the ion exchange resin with distilled water to remove the surface scum and impurities; filter and dry; ② Acidification modification: Soak the ion exchange resin raw material in an acid solution to obtain an acidified ion exchange resin; ③ Surface modification: The acidified ion exchange resin is placed in an amine modification solution, heated, cleaned and dried to obtain an ion exchange resin with an amino-modified surface; ④ Antibacterial modification: The aminated ion exchange resin is placed in a solution containing quaternary ammonium and epoxy groups. After the reaction, it is washed and dried to obtain an antibacterial ion exchange resin.
2. The method for preparing the antibacterial ion exchange resin according to claim 1, characterized in that: The particle size of the ion exchange resin in step ① is 0.3-1.2 mm.
3. The method for preparing the antibacterial ion exchange resin according to claim 2, characterized in that: The ion exchange resin in step ① has a volume exchange capacity of ≥1.4 mmol / mL, a water content of 40% to 60%, and a density of 0.7 to 0.8 g / mL.
4. The method for preparing the antibacterial ion exchange resin according to claim 1, characterized in that: The acid in step ② is a mixture of one or more of hydrochloric acid, nitric acid and sulfuric acid; the ion exchange resin raw material is immersed in the acid solution for 30 to 90 minutes.
5. The method for preparing the antibacterial ion exchange resin according to claim 4, characterized in that: The pH of the acid solution in step ② is 2-5.
6. The method for preparing the antibacterial ion exchange resin according to claim 1, characterized in that: In the amine-modified solution described in step ③, the solute is one or more of ethylenediamine, chitosan, piperazine, N-carboxymethyl chitosan, polyethyleneimine, polyallylamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyvinyl imidazole, p-aminobenzene, m-aminobenzene, and polyvinylpyrrolidone.
7. The method for preparing the antibacterial ion exchange resin according to claim 6, characterized in that: In the amine-modified solution of step ③, the solvent is water, or the solvent is a mixture of one or more of methanol, ethanol, acetone and water.
8. The method for preparing the antibacterial ion exchange resin according to claim 7, characterized in that: The concentration of the amine modified solution in step ③ is 0.5-5wt%.
9. The method for preparing the antibacterial ion exchange resin according to claim 1, characterized in that: The heating in step ③ is: heating in a water bath at 50-90° C. for 12-24 hours.
10. The method for preparing the antibacterial ion exchange resin according to claim 1, characterized in that: The concentration of the solution containing quaternary ammonium and epoxy groups in step ④ is 2-9wt%.
11. The method for preparing the antibacterial ion exchange resin according to claim 10, characterized in that: The solute of the solution containing quaternary ammonium and epoxy groups in step ④ is a mixture of one or more of glycidyltrimethylammonium chloride, glycidyltriethylammonium chloride and glycidyldimethyldodecylammonium chloride.
12. The method for preparing the antibacterial ion exchange resin according to claim 11, characterized in that: The solvent of the solution containing quaternary ammonium and epoxy groups in step ④ is water.
13. The method for preparing the antibacterial ion exchange resin according to claim 1, characterized in that: The reaction of step ④ is: reacting in a water bath at 35-80° C. for 6-12 hours.
Citation Information
Patent Citations
Production method of mesoporous tourmaline and polystyrene composite multi-component copolymerization ion exchange resin
CN106220770A